Before and After the Clean Water Act: How Science, Law, and Public Aspirations Drove Seven Decades of Progress in Maine Water Quality - Courtemanch, David; Davies, Susan; Johnson, Eileen; Schaffner, Rebecca; Suitor, Douglas (Maine Policy Review, 2023)
In the 1950s, Maine established a water quality classification system creating the conceptual scaffolding of a tiered system of management. Passage of the federal Clean Water Act in 1972 drove dramatic advances in science, technology, and policy leading to systematic improvement for the next five decades. Today’s tiered classification system provides a range of management goals from natural to various allowable uses. The state assigns uses and standards for each classification, incorporating physical, chemical, and biological indicators. This system has brought steady improvement in water quality, ecological condition, and overall value for human use. Visible evidence of improvement and adoption of these management alternatives have inspired a re-imagining of how Maine’s waters can benefit clean water-based businesses, recreation, and amenity development.